2022
DOI: 10.1007/s40257-022-00708-w
|View full text |Cite
|
Sign up to set email alerts
|

Switching Between Adalimumab Reference Product and BI 695501 in Patients with Chronic Plaque Psoriasis (VOLTAIRE-X): A Randomized Controlled Trial

Abstract: Background BI 695501 is an FDA-approved biosimilar to adalimumab reference product (RP). VOLTAIRE-X was a randomized clinical trial to assess outcomes with a biosimilar monoclonal antibody in line with the FDA requirements for designation as an ‘interchangeable’ biosimilar. Objective The aim of this study was to assess whether multiple switches between adalimumab RP and BI 695501 lead to equivalent pharmacokinetics and a similar safety and immunogenicity profile compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…VOLTAIRE-X (NCT03210259) was 1 of the first randomized controlled trials to report outcomes that met FDA criteria for interchangeable designation. 25 This 48-week phase 3 interchangeability trial randomized 238 patients with moderate-to-severe chronic PsO and receiving reference product Humira (adalimumab) to undergo switching to biosimilar Cyltezo (adalimumab-adbm) or receive continuous Humira. Results showed that switching 3 times between Cyltezo and Humira resulted in equivalent efficacy, PK, and immunogenicity, and comparable safety between the switching and continuous treatment groups.…”
Section: Overview Of Biosimilars For Immune-mediated Inflammatory Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…VOLTAIRE-X (NCT03210259) was 1 of the first randomized controlled trials to report outcomes that met FDA criteria for interchangeable designation. 25 This 48-week phase 3 interchangeability trial randomized 238 patients with moderate-to-severe chronic PsO and receiving reference product Humira (adalimumab) to undergo switching to biosimilar Cyltezo (adalimumab-adbm) or receive continuous Humira. Results showed that switching 3 times between Cyltezo and Humira resulted in equivalent efficacy, PK, and immunogenicity, and comparable safety between the switching and continuous treatment groups.…”
Section: Overview Of Biosimilars For Immune-mediated Inflammatory Dis...mentioning
confidence: 99%
“…If state law permits, an interchangeable biosimilar may be substituted by a pharmacist for its reference product without permission of the HCP. 18,25 Physician-mediated switching should be differentiated from nonmedical switching, which is defined as altering a treatment regimen in patients with stable disease for reasons such as drug formulary changes and/or cost reductions. 27 One of the concerns related to biosimilars in general and switching between a reference product and a biosimilar is immunogenicity.…”
Section: Overview Of Biosimilars For Immune-mediated Inflammatory Dis...mentioning
confidence: 99%
“…PROVIDER AND PATIENT KNOWLEDGE GAPS ON BIOSIMILARS severe chronic plaque psoriasis was then demonstrated in the phase 3 VOLTAIRE-X trial (NCT03210259). 48 VOLTAIRE-X data showed that switching several times between adalimumab-adbm and adalimumab reference product resulted in equivalent pharmacokinetics, efficacy, immunogenicity, and comparable safety in people with moderate to severe chronic plaque psoriasis. At week 32, the study met the primary end point, supporting the application of adalimumab-adbm as an interchangeable biosimilar for the adalimumab reference product.…”
Section: S231mentioning
confidence: 99%
“…There have been >90 switching studies performed with biosimilars which have not revealed any significant issues. 13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This continued surveillance must remain a focus of pharmacovigilance programs to monitor biosimilars as they are on the market. 34…”
Section: Introductionmentioning
confidence: 99%
“…There have been >90 switching studies performed with biosimilars which have not revealed any significant issues. 13,16-33…”
Section: Introductionmentioning
confidence: 99%